RANCANG BANGUN MESIN PEMISAH TUTUP GELAS MINERAL PADA UD. EKA JAYA - Setiyawan, Nandha; Androga, Frisco Merry; Robi Putra, Yopi Ramadhani (Program Kreativitas Mahasiswa - Teknologi, 2014)
The separation process of mineral glass lid on SME (UKM) partner still use manuallly method, it uses a razor blade. The purpose of this program (PKM â T) is to improve efficiency and effectiveness in separating process so that its productivity can be increased. This machine has easy operation, by pressing ON if it is being used and pressing OFF after using it. The method offered by our team to solve the problems uses several stages. Formulating the problems then create the machine, trial and repair it, training and maintenance it. The last is acceptance and monitoring. Based on the activities that have been done on schedule, our team can create separator machine with capacity 25 kg/h. It is quite practical and efficient to operate. The conclusion is the capacity of separation process 50 kg/ h by using this machine or increase from the previous capacity using conventional method, 25 kg/h. It means it will increase the price of the mineral glass and reduce the energy used for separation process.Keywords: Mineral water glass, separation, capacity